Local arrangement of microfibrillar-associated protein 5 with neurovascular and extracellular components in non- and ischemia-affected brain regions of mice - Höfling, Corinna; Roßner, Steffen; Flachmeyer, Bianca; Härtig, Wolfgang; Michalski, Dominik (Frontiers in Neuroscience, 2025)
Stroke often leads to death or functional impairment, and neuroprotective strategies are still lacking. Among the mechanisms contributing to tissue damage and yielding thus interest for therapeutic interventions, an affection of cytoskeletal elements has been considered. A first description of the microfibrillar-associated protein 5 (MFAP5) has yielded a fiber-like pattern and reduced immunosignals in the ischemic brain. However, details on region characteristics are lacking. This study thus aimed to explore local arrangements of MFAP5 with components of the neurovascular unit and extracellular matrix in non- and ischemia-affected neocortical brain regions of mice. Immunofluorescence labeling was used to visualize MFAP5 simultaneously with neurons, glial cells, vasculature, perineuronal nets, fibronectin, and the cytoskeletal elements neurofilament light chain (NF-L) and microtubule-associated protein 2 (MAP2). Fluorescence-based microscopy, confocal laser scanning microscopy, and 3D surface reconstruction served for analyses. MFAP5 was observed in a predominantly fiber-like and partially surrounding formation associated with neuronal processes and cell bodies. In the ischemic region, MFAP5 markedly diminished, but a few fiber-like structures were maintained with a thinned, partially fragmented, and twisted aspect. MFAP5 exhibited no clear regional association with microglia, astroglia, or parts of the vasculature and ECM. However, the local arrangement of MFAP5 and its change due to ischemia was comparable to that of NF-L and MAP2. This study comprehensively described MFAP5 after experimental stroke and identified similarities with MAP2 and NF-L. Thus, MFAP5 might represent an essential component of the neuronal cytoskeleton. Further research is needed to explore its functional properties and potential for neuroprotective approaches.